(untitled) (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Guillain-Barré Syndrome (GBS) is an acute immune-mediated polyradiculoneuropathy characterized by rapidly progressing muscle weakness. GBS usually follows a monophasic course, but rarely it can recur after an asymptomatic period of several months to years. Limited cases of recurrent GBS have been reported in the literature. We present two cases of recurrent GBS encountered in a tertiary care hospital. This case report describes the clinical presentation, diagnostic workup, management, and outcomes of two children of GBS who experienced recurrence. By presenting the cases, we aim to increase awareness of this rare presentation of GBS among healthcare professionals and enabletimely recognition and better outcomes for children with recurrent GBS. J Com Med Col Teachers Asso Jan 2024; 28(1): 37-40